Impact of Melatonin Supplementation in Women with Unexplained Infertility Undergoing Fertility Treatment - Javier Espino; María Macedo; Graciela Lozano; Águeda Ortiz; Carmina Rodríguez; Ana B. Rodríguez; Ignacio Bejarano (MDPI AG, 2019)
Unexplained infertility occurs when common causes for a couple’s inability to conceive have been excluded. Although origins of idiopathic infertility are still unclear, factors, such as an altered oxidative balance, are believed to be involved. Melatonin is an outstanding antioxidant reportedly present in the follicular fluid (FF), which has been suggested as a useful tool in the management of human fertility. Herein, we observed that intrafollicular concentrations of melatonin were blunted in women with unexplained infertility (UI), which was associated with a marked oxidative imbalance in UI patients’ FF. Based on these findings, this randomized pilot study was aimed at assessing whether exogenous melatonin ameliorated oxidative stress and improved in vitro fertilization (IVF) success rates in UI. Thus, 3 mg/day or 6 mg/day of melatonin were given to UI patients for a period spanning from the first appointment to control ovarian stimulation until the day of follicular puncture. Our results indicate that melatonin supplementation, irrespective of the two doses tested, ameliorated intrafollicular oxidative balance and oocyte quality in UI patients, and that this translated into a slight increase in the rate of pregnancies/live births. Therefore, although the indoleamine has shown therapeutic potential in this clinical setting, larger clinical trials in populations with different backgrounds are encouraged to corroborate the usefulness of melatonin.